THE EFFECT OF USING GOOGLE DOCS ON THE STUDENTS’ SKILL IN WRITING EXPOSITORY ESSAY ACROSS PERSONALITY LEARNING STYLE - Bagio Tjahjadi; Sintha Tresnadewi; Bambang Yudi Cahyono (Jurnal Pendidikan Humaniora, 2020)
Abstract: This research is aimed at (1) finding out whether the EFL students taught using Google docs show better writing ability than those taught without using Google docs, (2) discovering if there is a significant difference in writing ability between the introverted students and extroverted students taught using Google docs. This research involved two intact classes of ten graders in SMA Kristen Charis Malang consisting of 29 and 28 students respectively that were randomly selected to be the experimental and control group.  The experimental group worked collaboratively outside the class using Google docs whereas the control group worked in the face-to-face class. Both groups were assigned to compose an expository essay based on the topics given in the pre-test and post-test to reveal their writing achievement before and after the treatment. The results showed that the mean score of experimental group was significantly higher than that of the control group. When it comes to personality learning styles, there was no significant difference in the mean scores obtained by the extroverted students and introverted students.Keywords: google docs, writing ability, expository essay, personality, learning styles